Skema Pengalamatan Ip Address Pada Desain Jaringan Komputer Local Area Network (Lan) Menggunakan Metode Subnetting - Imam Asrowardi (Jurnal Ilmiah ESAI, 2008)
The use of IP address without a good planning can give rise to traffic which is hard to monitor that can decrease the network performance, problems in network management, and wasteful use of IP address.Â  The sub-netting concept is used in order to manage computer network designs so that network performance can be optimized. This study is conducted to apply the sub-netting concept in Local Area Network (LAN) designs. There are 440 computers distributed in some spots. The computers use IP address of C class with IP 192.168.1.0-192.168.4.0 in which eachÂ  network was divided into 4 sub networks that made each sub network covers 62 hosts with sub-net-mask 11111111.11111111.11111111.11000000 or with CIDR /26.Keywords : IP address, Sub netting, Network, Design.